Krisis Penyakit Tidak Menular pada Usia Muda: Dari Faktor Risiko ke Strategi Pencegahan - Marisa Syavitri Dilaga (Lombok Medical Journal, 2026)
Non-communicable diseases (NCDs) are increasingly burdening the productive-age population, indicating an epidemiological shift toward an earlier onset of chronic diseases. Both global and national levels, hypertension and diabetes show high trends among younger age groups, including at the regional level. This situation is driven by the accumulation of risk factors in adolescence, such as physical inactivity, unhealthy diets, sedentary behavior, smoking, and psychosocial stress, reflecting the multidimensional nature of NCDs. Therefore, prevention must be implemented comprehensively from adolescence through lifestyle interventions, supportive social environments, public policies that promote healthy behaviors, and active youth participation. The integration of mental health into primary care is also essential to strengthen long-term NCD control